Utility of mung bean powder as an ingredient in a dry mix beverage - Macaspac, Krissia Lou S. (College of Home Economics, University of the Philippines Diliman, 2013)
The study evaluated the utility of mung bean powder (MBP) as milk substitute in a dry mix beverage formulation. Initial works showed that using MBP produced through the soak-boil-dry (SBD) process resulted in beverages with better quality attributes; compared to that produced using the boil-dry (BD) method. Response surface analyses for the influence of the ingredients on quality attributes revealed that MBP and milk had varying individual and interactive effects of the measured quality acceptability parameters. Cost and nutritional quality evaluation showed that the identified most acceptable formulation is a cheaper alternative to milk, with nutritive value comparable to that of milk. The results established in this work may be significant in developing food products that may be applied in mass feeding, government-initiated feeding programs, or in disaster relief operations.